2018
DOI: 10.1007/s00267-018-1013-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Detection Methods and Vegetation Associations for Introduced Finlayson’s Squirrels (Callosciurus finlaysonii) in Italy

Abstract: Managing biological invasions requires rapid, cost-effective assessments of introduced species' occurrence, and a good understanding of the species' vegetation associations. This is particularly true for species that are elusive or may spread rapidly. Finlayson's squirrel (Callosciurus finlaysonii) is native to Thailand and southeastern Asia, and two introduced populations occur in peninsular Italy. One of the two introduced populations is rapidly expanding, but neither effective monitoring protocols nor relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Land‐use categories were grouped into broader classes (Supporting Information Table ) according to the ecology of the studied species and following the categories considered in the future land‐use change scenarios (Verburg et al, ). The four squirrel species live in forests, and show a different ability to move along tree lines, woodlots or shrubby areas (Ancillotto et al, ; Guichon & Doncaster, ; Mori et al, ; Wauters & Gurnell, ), thus forests and semi‐natural areas are considered areas suitable for dispersal and establishment. Artificial areas are semi‐permeable barriers since the four squirrel species are known to have established populations in urban areas (Ancillotto et al, ; Bertolino et al, ; Guichon & Doncaster, ; Mori et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Land‐use categories were grouped into broader classes (Supporting Information Table ) according to the ecology of the studied species and following the categories considered in the future land‐use change scenarios (Verburg et al, ). The four squirrel species live in forests, and show a different ability to move along tree lines, woodlots or shrubby areas (Ancillotto et al, ; Guichon & Doncaster, ; Mori et al, ; Wauters & Gurnell, ), thus forests and semi‐natural areas are considered areas suitable for dispersal and establishment. Artificial areas are semi‐permeable barriers since the four squirrel species are known to have established populations in urban areas (Ancillotto et al, ; Bertolino et al, ; Guichon & Doncaster, ; Mori et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The four squirrel species live in forests, and show a different ability to move along tree lines, woodlots or shrubby areas (Ancillotto et al, ; Guichon & Doncaster, ; Mori et al, ; Wauters & Gurnell, ), thus forests and semi‐natural areas are considered areas suitable for dispersal and establishment. Artificial areas are semi‐permeable barriers since the four squirrel species are known to have established populations in urban areas (Ancillotto et al, ; Bertolino et al, ; Guichon & Doncaster, ; Mori et al, ). Variables related to agricultural activities (e.g., permanent crops, rice fields, pastures, arable lands) were not considered because generally they represent a matrix not suitable for squirrels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been demonstrated that in the Maratea area, C. finlaysonii was responsible for bark stripping damage of Carob ( Ceratonia siliqua L., 1753), Quercus virgiliana ( Quercus virgiliana Ten.) , Holm ( Quercus ilex L., 1753), and Olive ( Olea europea L., 1753) [ 7 , 8 ]. The risk of extinction is very high for native species ( Sciurus vulgaris ) in Italy, and also the International Union for Conservation of Nature (IUCN) enrolled this species among those of the red list since 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Finlayson's squirrel is an arboreal rodent native to Thailand, Myanmar, Laos, Cambodia and Vietnam (Ancillotto et al, 2018). A few populations of this squirrel, introduced through the pet trade (Bertolino and Lurz, 2013), have established outside its native range in the last 35-40 years.…”
mentioning
confidence: 99%